Pancreatic cancer and fibrosis: Targeting metabolic reprogramming and crosstalk of cancer-associated fibroblasts in the tumor microenvironment - Li, Xin; Zhou, Jianbo; Wang, Xue; Li, Chunxi; Ma, Zifan; Wan, Qiaoling; Peng, Fu (Frontiers in Immunology, 2023)
Pancreatic cancer is one of the most dangerous types of cancer today, notable for its low survival rate and fibrosis. Deciphering the cellular composition and intercellular interactions in the tumor microenvironment (TME) is a necessary prerequisite to combat pancreatic cancer with precision. Cancer-associated fibroblasts (CAFs), as major producers of extracellular matrix (ECM), play a key role in tumor progression. CAFs display significant heterogeneity and perform different roles in tumor progression. Tumor cells turn CAFs into their slaves by inducing their metabolic dysregulation, exacerbating fibrosis to acquire drug resistance and immune evasion. This article reviews the impact of metabolic reprogramming, effect of obesity and cellular crosstalk of CAFs and tumor cells on fibrosis and describes relevant therapies targeting the metabolic reprogramming.